2019
DOI: 10.1093/ckj/sfy132
|View full text |Cite
|
Sign up to set email alerts
|

Implication of interleukin-2 receptor antibody induction therapy in standard risk renal transplant in the tacrolimus era: a meta-analysis

Abstract: Background Interleukin-2 (IL-2) antagonist has been used as an induction therapy in many centres in calcineurin inhibitor-sparing regimens. Tacrolimus has overwhelmingly replaced cyclosporine in the maintenance immunosuppressive protocols in many transplant centres. The aim of our study and meta-analysis is to explore the effect of IL-2 induction therapy on the rate of rejection and patient and graft survival in standard-risk renal transplant patients with tacrolimus-based maintenance immunot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…We have read with great interest the article written by Ali et al [1] titled: “Outcomes of Interleukin-2 Receptor Antagonist Induction Therapy in Standard-Risk Renal Transplant Recipients Maintained on Tacrolimus: A Systematic Review and Meta-Analysis.” This meta-analysis included 12 RCTs and showed significant results and concluded that in standard-risk transplant patients maintained on tacrolimus and MMF, basiliximab induction therapy had no additional benefit compared to no-induction therapy. This conclusion was observed in previous retrospective studies [2, 3].…”
supporting
confidence: 88%
“…We have read with great interest the article written by Ali et al [1] titled: “Outcomes of Interleukin-2 Receptor Antagonist Induction Therapy in Standard-Risk Renal Transplant Recipients Maintained on Tacrolimus: A Systematic Review and Meta-Analysis.” This meta-analysis included 12 RCTs and showed significant results and concluded that in standard-risk transplant patients maintained on tacrolimus and MMF, basiliximab induction therapy had no additional benefit compared to no-induction therapy. This conclusion was observed in previous retrospective studies [2, 3].…”
supporting
confidence: 88%
“…The authors found no additive benefit for interleukin-2 induction therapy in the standard risk population. Similar results were shown in the previous registry and in retrospective studies [2, 3]. The authors used a broad definition for standard-risk renal transplant which included HLA mismatches of <5.…”
supporting
confidence: 67%
“…Several studies have been performed to assess the outcomes of IL-2 receptor antagonist induction therapy in standard risk population in tacrolimus era; most of these are retrospective studies with small sample size [10]. To the best of our knowledge, this is the first study to be performed in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…The study population were restricted to standard risk patients who were maintained on tacrolimus-based immunotherapy. Standard risk transplants were defined as patients with < 2DR mismatch, calculated reaction frequency (CRF) < 20%, live donors or donors after brain death and patients with no previous renal transplantation [8,[10][11][12][13]. CRF is an indication of the level of sensitization and reflects the percentage of blood group identical, HLA incompatible donors [14].…”
Section: Methodsmentioning
confidence: 99%